The effects of different root canal instrumentation techniques on dentinal microcracks formation: A narrative review - Faisal T Alghamdi; Adel S Alqahtani; Othman M Baradwan; Fahad O Almolla; Omar R Alkhattab; Khalid A Merdad (Saudi endodontic journal, 2022)
Introduction: The influence of intracanal instrumentation technique on microcrack formation is a debatable subject. This review aimed to review the effect of different root canal instrumentation techniques (hand, continuous rotary, reciprocal rotary, adaptive, and self-adjusting file techniques) on microcracks formation and evaluate whether the incidence of cracks formation differs between destructive and nondestructive evaluation methods. Materials and Methods: All in vitro studies comparing the influence of at least two different instrumentation techniques were searched for this narrative review in PubMed, Scopus, and Google Scholar databases. The search included articles that were published from 2016 to 2020. The search was carried out by six independent reviewers in this review. Results: A total of twenty-five (n = 25) articles met the eligibility criteria. Only six studies showed the absence of new cracks development in 320 human teeth according to the instrumentation technique while the majority of the studies (n = 19) illustrated the presence of new cracks development in 1696 teeth. The results of this review showed that nondestructive methods may be less likely to cause microcracks than destructive methods. Conclusions: The number of dentinal microcracks varies depending on the type of instrumentation techniques and evaluation methods used. Therefore, in destructive evaluation methods, root canal instrumentation with hand, reciprocating, rotary, adaptive, and self-adjusting systems resulted in the development of more new dentinal microcracks than nondestructive methods.